Visual Content Strategy Analysis: Enhancing Consumer Engagement in Wardah’s Marketing Approach - Pranasa, Risyaf; Lazuardi, Ashar; Putrajip, Mohamad (LPPM Institut Bisnis dan Informatika Kesatuan, 2023)
This research aims to find out the visual content strategy used by Wardah in building prospective consumers’ purchase requests. This research method uses a qualitative method. This research is descriptive analysis, which is a type of research that provides an overview and describes as clearly as possible the situation without treating the object being studied. Secondary data previously obtained information collected from indirect or second-hand sources, such as government written sources, libraries, official documents, books, research results. The research results obtained include; The packaging used by Wardah is always easy to carry anywhere. Apart from that, Wardah’s distinctive packaging can help differentiate its products from its competitors in the market. Additionally, custom pricing strategies can also be used to respond to market trends or celebrate special events such as holidays, company birthdays, or other celebrations. Wardah always provides education and information regarding facial health and facial skin problems. The visual content on Wardah’s Instagram account has its own meaning and purpose in increasing consumer purchasing power.